Developing the Ability of Reading and Writing in Spelling Thai Language Words by Utilizing the Hunter’s Model of Teaching for Grade 1 Students in Mueang Moeiwadee Kindergarten School, Moei Wadi District, Roi Et Province - Chaithongsri, Natthavadee; Pharanat, Wanida (Journal of Roi Et Rajabhat University, 2024)
This research aimed to 1) study the effectiveness of learning management in Thai reading and writing spelling abilities according to the Hunter’s model, with a target effectiveness of (E1/E2) 75/75; 2) compare the post-intervention reading spelling abilities in Thai against a criterion of 75% after learning management according to the Hunter’s model; and 3) compare the post-intervention writing spelling abilities in Thai against a criterion of 75% after learning management according to the Hunter’s model. The samples used in the research were 16 students from Grade 1, room 2, who are studying in the second semester of the academic year 2023 of Mueang Moeiwadi Kindergarten School, under the Roi Et Primary Educational Service Area Office 3, selected through simple random sampling. Research instruments were: 1) Eight teaching plans based on the Hunter’s model, totaling 16 hours, 2) A test measuring Thai reading spelling ability with 10 items, and 3) A test measuring Thai writing spelling ability with 10 items. The research employed a single-group only post-test experimental design. Statistical analysis included mean, standard deviation, and single-group t-test. The research findings revealed that: 1) The effectiveness of learning management according to the Hunter’s model had an effectiveness of E1/E2 = 82.42/80.30; 2)The students have significantly higher ability in Thai word reading after the instructional intervention, exceeding the criterion of 75% at the statistical significance level of .05; and 3) The students have significantly higher ability in Thai word writing after the instructional intervention, exceeding the criterion of 75% at the statistical significance level of .05.